Development and Performance Evaluation of a Bullock Drawn Sprayer - Singh, R C; Singh, V V; Dubey, U C (Journal of Agricultural Engineering, 2009)
A bullock drawn sprayer was developed considering the agronomical and functional requirement for application of chemicals on soybean and other field crops. A commercially available pressure vessel of 9498 cmÂ³ was adopted to maintain the required fluid pressure during spraying in the field. Two reciprocating pumps of 127 cm3 swept volume were provided to create working pressure range of 300-350 kPa inside the pressure vessel at 94-100 rpm. The unit was tested for spraying of chemical in the laboratory and on soybean crop with a pair of Malvi breed of bullocks. During laboratory test, the uniformity coefficient of droplets ranged from 2.2 to 2.7 and was within the acceptable level of 4.0 for all the six nozzles. In field testing, the average discharge of six nozzles varied from 481.6 to 529 ml/min with average boom discharge of 3.03 l/min at pressure of 343 ± 2.5 kPa. The mean discharge was 505 ml/min per nozzle with coefficient of variation of 3.09%. Effective field capacity and power requirement to operate the sprayer was 0.56 ha/h and 0.68 kW respectively.